Thermodynamical length scales temperatures correlation for the Ginzburg-Landau theory - Bousnane, Z.; Merabtine, N.; Benslama, M.; Bousaad, F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
The emergence of the superconducting state must obey to a variational principle representations, as considered in the classical schemes, the invariance of the extremum values, according to the use of thermodynamical functions, will suggest an internal coherence governing the jumps realized by the symmetries, against the non-univoc determination permitted by the variations of the thermodynamical parameters. The uncertainties for macroscopic states must be associated to the existence of “macroscopicity levels”, considering the interaction between cooled and cooling, the macroscopic state of each one, will be considered as a combinatory length scales interactions. The reversed role between cooled and cooling suggests that near transition point Eδ will be spent in c²∆Γ . The thermodynamical functions are obtained each from other by the uncertainty principle.